2018
DOI: 10.3390/jcs2040068
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modelling and Validation of Thermomechanical Behaviour for Layered Aluminium Parts Made by Composite Metal Foil Manufacturing

Abstract: The paper presents finite element modelling and thermomechanical analysis on the tensile properties of layered aluminium 1050 metal foil parts made by composite metal foil manufacturing. In this paper, a three-dimensional finite element model was developed and validated through experiments to analyse thermal effects on the tensile properties of 200-μm-thick aluminium 1050 metal foils. The effects of thermal stress and strain were studied by carrying out transient thermal analysis on the heated plates used to j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(16 reference statements)
2
5
0
Order By: Relevance
“…It will always be the metal with the most negative anodic index which will ultimately suffer from corrosion when galvanic incompatibility is in play. The results obtained here are also in-line with our previous work with other composites made by CMFM but tested for only 24 h [19,26]. However, it is recommended that longer tests are carried out possibly spanning a month or three months to assess the integrity of the bond/foil interface as after 7 days, it has been concluded that galvanic corrosion does not adversely affect the composites made by CMFM.…”
Section: Results From Corrosion Testingsupporting
confidence: 89%
See 4 more Smart Citations
“…It will always be the metal with the most negative anodic index which will ultimately suffer from corrosion when galvanic incompatibility is in play. The results obtained here are also in-line with our previous work with other composites made by CMFM but tested for only 24 h [19,26]. However, it is recommended that longer tests are carried out possibly spanning a month or three months to assess the integrity of the bond/foil interface as after 7 days, it has been concluded that galvanic corrosion does not adversely affect the composites made by CMFM.…”
Section: Results From Corrosion Testingsupporting
confidence: 89%
“…This experiment validated the applicability of numerical simulations to produce parts using CMFM. This result is in-line with the comparison done in our previous work where aluminum foils of 200-micron thickness were utilized [26]. This clearly demonstrate that numerical analysis can be utilized for producing composites using CMFM with different foil thicknesses and geometries.…”
Section: Validation For Al Compositesupporting
confidence: 90%
See 3 more Smart Citations